The dragon prince. [3], Puzzle House - Ehasz, Aaron; Wartman, Peter; Richmond, Justin (Ehasz, Aaron. Dragon prince, 2023)
"Learning magic is no easy thing, even for young Claudia. Despite a bit of help from a book of spells created by Kpp'Ar, her father's former mentor, it's all she can do to keep things from blowing up in her face--often with spectacularly messy results. But a spell book isn't the only thing that Kpp'Ar left behind when he suddenly and mysteriously vanished. In his wake stands the Puzzle House, a bizarre tower full of magical traps, tricks, contraptions, and--what else--puzzles. Claudia is sure that the old mage left a gift for her and her brother, Soren, somewhere deep within its walls, and she is determined to find out exactly what it is. Can Claudia and Soren uncover all the mysteries hidden within the Puzzle House? Or will they discover a darkness that will change them forever?"--Back cover.